A brief report on older people's experience of cybercrime victimization in Mumbai, India. Issue 4 (20th October 2019) - Tripathi, Kartikeya; Robertson, Sarah; Cooper, Claudia
ABSTRACT: As internet penetration increases in Lower and Middle Income Countries (LMIC), more older people are now conducting financial transactions online and using social media to stay in touch with family and friends. We discuss concerns that existing financial regulations and controls in India may afford older people insufficient protection from cybercrime, using qualitative interviews from our recent study exploring older people's experiences of cybercrime in Mumbai.